A randomized control trial of interventions in school-aged children with auditory processing disorders. - Sharma, Mridula; Purdy, Suzanne C; Kelly, Andrea S (International Journal of Audiology, 2012)
Objective: The primary purpose of the study was to compare intervention approaches for children with auditory processing disorder (APD): bottom-up training including activities focused on auditory perception, discrimination, and phonological awareness, and top-down training including a range of language activities. Another purpose was to determine the benefits of personal FM systems. Design: The study is a randomized control trial where participants were allocated to groups receiving one of the two interventions, with and without personal FM, or to the no intervention group. The six-week intervention included weekly one-hour sessions with a therapist in the clinic, plus 1-2 hours per week of parent-directed homework. Study sample: 55 children (7 to 13 years) with APD participated in the study. Intervention outcomes included reading, language, and auditory processing. Results: Positive outcomes were observed for both training approaches and personal FM systems on several measures. Pre-intervention nonverbal IQ, age, and severity of APD did not influence outcomes. Performance of control group participants did not change when retested after the intervention period. Conclusions: Both intervention approaches were beneficial and there were additional benefits with the use of personal FM. Positive results were not limited to the areas specifically targeted by the interventions.